A review of family influences on travel decision making - Osman, F.N.; Hashim, H.; Nezakati, Hossein *; Hussin, S.R.; Aziz, Y.A.; Raja-Yusof, R.N. (2014)
Environmental concerns are evident in the increasingly ecologically aware marketplace. One of the competitive advantages of hotels is the implementation of a green management, which can increasingly resolve environmental issues and may play an important role in this industry. In Malaysia, increasing the number of tourists is one of the important factors that affects the country’s economy and helps achieve its plan of 2020. Based on the theory of planned behavior (TPB) and marketing mix tools, this study reviews the factors that influence the attitudes and behavior intentions of consumers toward choosing green hotels in Malaysia. The methodology of this study is based on secondary data, and it aims to understand the TPB factors and marketing mix in the hospitality sector. The results of this study are deemed beneficial to researchers, hotel managers, and policy makers in the tourism industry, particularly in the context of environmentally friendly hotels in Malaysia